Increasing Teacher’s Ability to Develop Teaching and Learning Material Based on Higher Order Thinking Skills (HOTS) - Winarti, Winarti (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
Learning with teaching material based on higher-order thinking skill could improve the learners’ understanding. This community service research provides training and mentorship for physics educators to compose innovative physics teaching materials. Twenty educators from Islamic Senior High Schools joined the community service activity. The success of the activity was observable on the educators while mentoring the teaching material preparation. The educators have high interest on the activities. They had the same objectives in the activity to create innovative teaching materials. Thus, the students while learning physics had high learning motivation. Generally, the program implementation remained within the activity orders, the workshop and training to develop teaching materials and HOTS-based assessment. The developed teaching material made the teachers enthusiastic to develop the HOTS-based teaching material. The products consisted of three HOTS-based modules, one book, one HOTS-based assessment, and three copyrighted works of the teachers.